2022
DOI: 10.1002/fsn3.2879
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the protein degradation during the broad bean fermentation process

Abstract: Broad bean fermentation is of vital importance in PixianDouban (PXDB) production, as well as a key process for microorganisms to degrade protein, which lays the foundation for the formation of PXDB flavor. In this study, two fungi and bacteria were screened, and their morphology, molecular biology, growth, and enzyme production characteristics were analyzed, and then they were applied to the broad bean fermentation simulation system. The protein, peptide, amino acid, amino nitrogen, and sodium dodecyl sulfate‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Organic acids have a strong influence on flavor balance, chemical stability, pH, and sample quality 6 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Organic acids have a strong influence on flavor balance, chemical stability, pH, and sample quality 6 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Organic acids have a strong influence on flavor balance, chemical stability, pH, and sample quality. 6 As shown in Fig. 3, a total of seven acids (including oxalic acid, tartaric acid, malic acid, lactic acid, citric acid, fumaric acid, and succinic acid) were detected.…”
Section: Characterizing the Non-volatiles Compoundsmentioning
confidence: 93%
See 2 more Smart Citations
“…Bacterial strains have significantly higher protease and peptidase activity compared to yeast and molds (Zhou et al 2021 ). However, simulations of the fermentation of broad bean paste by two salt-tolerant fungi and two salt-tolerant bacteria have shown that the total protein, peptide, and amino acid content is higher in the fungal group than in the bacterial group (Lin et al 2022 ). Fungal-derived enzyme systems have demonstrated greater albumin and glutenin activity under neutral conditions.…”
Section: Examples Of Microbial-derived Stps Applied To High-salt Trad...mentioning
confidence: 99%